POTENTIAL OF VARIOUS INDONESIAN MEDICINAL PLANTS TO INHIBIT THE GROWTH OF Aeromonas hydrophila BACTERIA - Kurniawan, Ronal; Windarti, Windarti; Effendi, Irwan; Putri, Mega Novia; Syahputra, Tomi; Gusriansyah, Dimas; Riswan, M (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Aeromonas hydrophila is a gram-negative bacterium that can infect fish and is zoonotic to humans. Efforts to prevent this bacterial infection can be made using herbal plants due to the content of secondary metabolite compounds. This study aims to explore plants that have the potential as antibacterials, especially A. hydrophila bacteria. This research was conducted in February 2024 at the Marine Biotechnology Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau. The experimental method used included the stages of preparation of plant leaf samples and antibacterial tests using Kirby-Bauer discs. The plants used were the leaves of senduduk (Melastoma malabathricum), kantong semar (Nepenthes sp), lime (Citrus aurantifolia), belimbing bukit (Acetosella barreligeri), sirsak (Annona muricata), mucuna (Mucuna bracteata), Israel grass (Asystasia gangetica), and miana (Coleus scutellariodes). The results showed that the leaves of kantong semar, senduduk, and belimbing bukit could inhibit bacterial growth in a strong category. In contrast, the leaves of sirsak, mucuna, Israel grass, miana, and lime were classified as moderately inhibiting the growth of A. hydrophila bacteria. In conclusion, these herbal plants can potentially prevent A. hydrophila bacterial infection